Clinical classification and long‐term outcomes of seronegative coeliac disease: a 20‐year multicentre follow‐up study. Issue 10 (8th September 2021) - Schiepatti, Annalisa; Rej, Anupam; Maimaris, Stiliano; Cross, Simon S.; Porta, Petra; Aziz, Imran; Key, Tim; Goodwin, John; Therrien, Amelie; Yoosuf, Shakira; Leffler, Daniel A.; Silvester, Jocelyn A.; et al.
Summary: Background: Seronegative coeliac disease is poorly defined. Aims: To study clinical phenotypes and long‐term outcomes of seronegative coeliac disease in a multicentre cohort over 20 years. Methods: Seronegative coeliac disease was diagnosed in HLA‐DQ2/DQ8‐positive patients with villous atrophy (VA), negative IgA endomysial (EmA), tissue transglutaminase (tTG) and deamidated‐gliadin antibodies (DGP), clinical and histological response to a gluten‐free diet (GFD), and no alternative causes for VA. In patients with IgA deficiency, coeliac disease was diagnosed through VA, positive IgG EmA/tTG/DGP and clinical/histological response to a GFD (coeliac disease+IgAd). Patients with seropositive coeliac disease served as controls. Results: Of 227 patients previously diagnosed with seronegative coeliac disease, true seronegative coeliac disease was confirmed in 84, coeliac disease+IgAd in 48, and excluded in 55. Lack of follow‐up duodenal biopsy precluded diagnosing seronegative coeliac disease in 40 patients. 2084 patients with seropositive coeliac disease served as controls. True seronegative coeliac disease had more severe symptoms at diagnosis and a higher risk of complications (HR 10.87, 95% CI 6.11‐19.33, P < 0.001) and mortality (HR 2.18, 95% CI 1.12‐4.26, P < 0.01) than seropositive coeliac disease. There were no differences between true seronegative coeliac disease and coeliac disease+IgAd. On multivariate analysis, age at diagnosis, lack of clinical response to a GFD, true seronegative coeliac disease, coeliac disease+IgAd, and classical presentation predicted complications. Age at diagnosis, complications and absence of clinical response to a GFD predicted mortality. Conclusions: Seronegative coeliac disease has a more aggressive disease phenotype than seropositive coeliac disease. These data argue against over‐reliance on serology for the diagnosis of coeliac disease and support a strict clinical and histologic follow‐up in seronegative coeliac disease. Abstract :